Physical Properties and Oxidative Status of Concentrated-from-Fish Oils Microencapsulated in Trehalose/Sodium Caseinate Matrix - Álvarez Cerimedo, María Soledad (2014)
Foods supplemented with omega-3 fatty acids have attracted much attention in the past decade. However, it is difficult to protect polyunsaturated fatty acids from oxidation. Microencapsulation is a technological process used with the aim to protect oils against oxidation or chemical deterioration, to mask unpleasant flavors or retain aromas, and/or to powder polyunsaturated fatty acids for food fortification purposes. The objective of this study was to analyze physical properties and oxidation status of microencapsulated concentrated-from-fish oils. Powders were prepared from emulsions formulated with 10 wt.% of concentrated-from-fish oils as fat phase and 20 or 30 wt.% trehalose solution that also contained 0.5, 2.0, or 5.0 wt.% sodium caseinate as aqueous phase. Encapsulation efficiency was higher for powders coming from 20 wt.% trehalose emulsions, and the percentage of retention of core material increased with increasing sodium caseinate concentration. The powder prepared from 20 wt.% trehalose and 5 wt.% sodium caseinate showed the highest retention of core material. This powder had lower water content and an amorphous matrix. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry method, used for this new application, allowed proving that trehalose/sodium caseinate matrix was efficient for microencapsulation of polyunsaturated oils and that concentrated-from-fish oils was protected from oxidation in powder form. Spectra were very similar to the original oil without any treatments. Most likely, the oxidation products found when core material was extracted were formed during extraction steps.